Does criminal justice stigma affect health and health care utilization? A systematic review of public health and medical literature. Issue 3 (15th July 2020) - Martin, Karin; Taylor, Andrew; Howell, Benjamin; Fox, Aaron
Abstract : Purpose: This paper aims to determine whether criminal justice (CJ) stigma affects health outcomes and health care utilization. Design/methodology/approach: The authors reviewed medical and public health literature through May 2020. Structured terms were used to search four databases identifying articles that related to CJ stigma. Included articles were in English, examined CJ stigma and had people with CJ involvement as subjects. The studies without health outcomes were excluded. Quantitative and qualitative studies were reviewed and assessed for bias. Results were synthesized into a systematic review. Findings: The search yielded 25 studies relating to CJ stigma and health. Three stigma domains were described in the literature: perceived or enacted, internalized and anticipated stigma. Tenuous evidence linked CJ stigma to health directly (psychological symptoms) and indirectly (social isolation, health care utilization, high-risk behaviors and housing or employment). Multiple stigmatized identities may interact to affect health and health care utilization. Research limitations/implications: Few studies examined CJ stigma and health. Articles used various measures of CJ stigma, but psychometric properties for instruments were not presented. Prospective studies with standard validated measures are needed. Practical implications: Understanding whether and how CJ stigma affects health and health care utilization will be critical for developing health-promoting interventions for people with CJ involvement. Practical interventions could target stigma-related psychological distress or reduce health care providers' stigmatizing behaviors. Originality/value: This was the first systematic review of CJ stigma and health. By providing a summary of the current evidence and identifying consistent findings and gaps in the literature, this review provides direction for future research and highlights implications for policy and practice.